2015
DOI: 10.1002/mgg3.165
|View full text |Cite
|
Sign up to set email alerts
|

Testicular dysgenesis/regression without campomelic dysplasia in patients carrying missense mutations and upstream deletion of SOX9

Abstract: SOX9 haploinsufficiency underlies campomelic dysplasia (CD) with or without testicular dysgenesis. Current understanding of the phenotypic variability and mutation spectrum of SOX9 abnormalities remains fragmentary. Here, we report three patients with hitherto unreported SOX9 abnormalities. These patients were identified through molecular analysis of 33 patients with 46,XY disorders of sex development (DSD). Patients 1–3 manifested testicular dysgenesis or regression without CD. Patients 1 and 2 carried probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The enhancer region exists in up to 2.0 Mb upstream of SOX9, and the chromosome translocation that results in CD or ACD exists at 50-375 kb, 379-459 kb, 585-932 kb, and 1.02-1.20 Mb upstream of SOX9. These are all a part of the locus 17q24.3 (Gordon et al 2014;Karaer et al 2014;Kim et al 2015;Katoh-Fukui et al 2015;Castori et al 2016). In the present case, a FISH analysis found that the breakpoint existed at chromosome 17q24.2, which has never been reported with respect to CD (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…The enhancer region exists in up to 2.0 Mb upstream of SOX9, and the chromosome translocation that results in CD or ACD exists at 50-375 kb, 379-459 kb, 585-932 kb, and 1.02-1.20 Mb upstream of SOX9. These are all a part of the locus 17q24.3 (Gordon et al 2014;Karaer et al 2014;Kim et al 2015;Katoh-Fukui et al 2015;Castori et al 2016). In the present case, a FISH analysis found that the breakpoint existed at chromosome 17q24.2, which has never been reported with respect to CD (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Missense mutations are almost always located in the HMG domain or SOXE dimerization domain. The only two missense mutations reported in the SOX9 TAC domain (R394G and R437C) caused testicular dysgenesis, but no sex reversal and no campomelic dysplasia, thus a less severe disease than that caused by allele deletions (62). To our knowledge, no missense mutations or in-frame microdeletions causing a developmental disease have been reported for the SOXE TAM domain and for the SOXE/SOXF EΦ[D/E]QYΦ motif.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence data were analyzed as described previously [Katoh-Fukui et al, 2015]. In this study, we focused on 32 genes known to be involved in the regulation of the HPG axis [Izumi et al, 2014;Macedo et al, 2016].…”
Section: Molecular Analysismentioning
confidence: 99%